Menyusun Program Pelatihan Bagi Karyawan - Mochammad Tofan (Pusat Riset dan Inovasi Nasional, 2021)
The purpose of this research is to describe the process of preparing training programs that can be provided by organizations to employees. The research method is qualitative with a theoretical study approach developed from Gerry Dessler's theory. Data collection techniques with documentation. Data processing with reduction, data presentation and data conclusion. Data validity with credibility through source triangulation. The results of the research show: training is an organizational way of improving the work ability of employees through coaching and mentoring by an expert. Training within the organization is structured as follows: first, analysis of training needs, by identifying the importance of conducting training based on employee performance gaps with organizational standards. Second, design the training, by arranging schedules, materials, presenters, time, equipment and so on needed to make the training program a success. Third, the development of materials prepared by adjusting the goals of the organization and the need for increasing employee competence. Fourth, the implementation of the training, taking into account the training methods, the flow of material delivery and discussion as well as closing the training process. Fifth, evaluation of training, by evaluating the process, results and impact of training on the organization and employees.